(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The increasing integration of personal smart devices into military operations has significantly expanded the attack surface, introducing critical security vulnerabilities. This paper explores how smart devices can compromise operational security (OPSEC) through unauthorized data leaks, cyber exploitation, and geolocation tracking. It examines real-world incidents, including security breaches during the Russian-Ukrainian conflict and the exposure of military bases via fitness tracking applications. Additionally, the study analyses adversarial tactics that leverage AI-driven OSINT and behavioural analytics to exploit smart device vulnerabilities. Finally, mitigation strategies, including policy recommendations and technical countermeasures, are discussed to enhance the cybersecurity posture of military personnel and operations.